Genome-wide identification and expression analysis of SWI1 genes in Boechera species. (June 2016) - Sezer, Fatih; Yüzbaşioğlu, Gözde; Özbilen, Aslıhan; Taşkin, Kemal M.
Graphical abstract: Highlights: We found no evidence for a naturally-occurring apomixis SWI1 allele. The expression levels of SWI1 mRNA in apomicts was higher than in sexuals. The molecular components controlling apomixis in Boechera spp. are not related to the SWI allele, but can be explained by investigating the role of epigenetic regulators. Abstract: As a mode of reproduction in plants, apomixis leads to the generation of clones via seeds. Apomictic plants form viable diploid female gametes without meiosis (apomeiosis) and produce embryos without fertilization (parthenogenesis). Apomeiosis, as a major component of apomixis, has recently been reported in some Arabidopsis thaliana mutants; dyad mutants of SWI1 showed developmental processes common to apomeiosis, such as producing functional diploid gametes. However, the orthologs of SWI1 genes in natural apomicts has not been previously reported. To identify the relationship between the SWI1 gene and the apomeiosis process, we isolated and sequenced SWI1 orthologs from Boechera species, including apomictic and sexual species. Boechera species are close relatives of A. thaliana and thus are advantageous model species for apomixis research. The SWI1 cDNAs were obtained by RT-PCR from apomictic and sexual Boechera young flower buds. We sequenced partial SWI1 transcripts that were 650 bp for B. holboellii and 684 bp for B. stricta . These SWI1- like sequences showed 86% similarity for B. holboellii and 92% for B. stricta to the A. thaliana SWI1 transcript. We also used available genome data and amplified genomic sequences for SWI1 orthologs in B. holboellii and B. stricta . The predicted proteins contain a phospholipase C domain and a nuclear localization signal. Sequence analysis did not show significant mutations related to apomixis, and phylogenetic analysis showed that SWI1 -like sequences were common across plant families, regardless of the presence of a sexual or apomictic reproduction system. We also investigated the expression levels of SWI1 mRNA in the B. holboellii and B. stricta young unopened flower buds and found that relatively high levels of expression occurred in apomicts.